1993
DOI: 10.1159/000139046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Treatment with Losartan Potassium (DuP 753) on the Elevation of Blood Pressure during Chronic Exposure of Rats to Cold

Abstract: Elevation of diastolic, systolic, and mean blood pressures and cardiac hypertrophy occur in rats exposed to cold (5°C) for 1-3 weeks. The renin-angiotensin-aldosterone system is believed to play a role in the development of cold-induced hypertension since plasma renin activity increases within the first 2 weeks, presumably initiating the hypertensive process, and then returns to control level. The present study was designed to assess the role of angiotension II (Ang II) in the hypertensive process by chronic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…The blood pressure (116Ϯ4 mm Hg) of the cold-exposed Agt-KO mice was at the level of the WT mice kept in warm (25°C, room temperature) at 5 weeks after exposure to cold. Consistently, our previous studies showed that the antihypertensive agents, such as propranolol, 18 captopril, 29 losartan potassium, 30 and L-arginine, 42 effectively reduced or prevented the coldinduced elevation of blood pressure but failed to prevent or attenuate cardiac hypertrophy. Thus, the occurrence of coldinduced cardiac hypertrophy is independent of either pressure overload or tachycardia.…”
Section: Discussionsupporting
confidence: 79%
“…The blood pressure (116Ϯ4 mm Hg) of the cold-exposed Agt-KO mice was at the level of the WT mice kept in warm (25°C, room temperature) at 5 weeks after exposure to cold. Consistently, our previous studies showed that the antihypertensive agents, such as propranolol, 18 captopril, 29 losartan potassium, 30 and L-arginine, 42 effectively reduced or prevented the coldinduced elevation of blood pressure but failed to prevent or attenuate cardiac hypertrophy. Thus, the occurrence of coldinduced cardiac hypertrophy is independent of either pressure overload or tachycardia.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies from our laboratory indicate that CICH is independent of pressure overload because prevention or attenuation of CIH does not attenuate CICH. [30][31][32]37,40,42 The present finding that the occurrence of CICH preceded that of CIH further reveals the disassociation of CICH and CIH. c-myc antisense on cold-induced cardiac hypertrophy M Bello Roufai et al…”
Section: Discussionsupporting
confidence: 64%
“…Numerous studies have shown that the sympathetic nervous system (SNS) or the rennin-angiotensin system (RAS) is not involved in CICH as evidenced by the fact that blockade of a-or b-adrenergic receptors or inhibition of the RAS at different levels does not attenuate CICH. 30,32,37,40,42,45 It was found that circulating levels of thyroid hormones (T 3 and T 4 ) were increased by cold exposure and may be involved in CICH. 46 A cell culture study indicated that thyroid hormone-induced myocyte hypertrophy requires p38 mitogen-activated protein kinase (p38MAPK).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that the blood-borne RAS either prevents or attenuates CIH. 5,6 The mechanism also appears to involve both peripheral tissue and central RAS because there is increased mRNA for AGT and/or AT 1 -R in brain and peripheral tissues, 7 increased spontaneous drinking response, and increased dipsogenic response to acute administration of Ang II either centrally or subcutaneously. 8 The receptors for Ang II in the diencephalon of rats have been correlated directly with the drinking response to Ang II.…”
mentioning
confidence: 99%